Evaluating Community Pharmacists’ Dyspepsia Knowledge: A Crosssectional Study in Tehran, Iran - Abbasinazari, Mohammad; Salamzadeh, Jamshid; Eshraghi, Azadeh; Belbasi, Vahid; Ashnagar, Arezoo (Reviews on Recent Clinical Trials, 2017)
Background: Dyspepsia is one of the most frequent ailments in the Iranian community. Fuelled by a growing interest in understanding drugs and self-medication for common conditions such as dyspepsia, the public increasingly seeks health advice from professionals such as community pharmacists. The purpose of our study was to assess dyspepsia-related knowledge of pharmacists in Iran. Methods: This cross-sectional study has been done among 200 community pharmacists working in Tehran, Iran, and conducted through a survey questionnaire, which consisted of questions about demographic information and knowledge of dyspepsia. The validity and reliability of the questionnaire were also evaluated. The main results estimated the knowledge of pharmacists about dyspepsia, and the relationship between pharmacists’ demographic and practice characteristics and their knowledge of dyspepsia. Results: The mean (± SD) age of participants was 41.56 ± 13.90 years, and the mean score of knowledge was 9.32 ± 2.13 out of 17 points. Our results showed a statistically significant negative relationship between knowledge levels and both age and years of experience (p = 0.002 and p = 0.033, respectively). Conclusion: According to the research, the mean knowledge level of Iranian pharmacists, in terms of correct responses for dyspepsia questions, was just over half of the possible points. Thus it was concluded that improvement in the knowledge of dyspepsia among pharmacists would improve the quality of patient services, especially because of the high prevalence of dyspepsia among the public and their frequent referral to community pharmacists for taking over-the-counter medication.
Keywords: pharmacist